THE IMPACT OF ENGLISH SONG IN VOCABULARY LEARNING : A PRE-EXPERIMENTAL STUDY AT A JUNIOR ISLAMIC BOARDING SCHOOL - Hikmah Pravitasari; Amila Yashila Rahmah (Universitas Wiralodra, 2024)
Pre-experimental design with one group pre-test and post-test was used in this study to determine whether there is any positive or negative effect on students' vocabulary mastery after they are taught using English songs. This study's instruments were a written vocabulary test and a field note. The researchers employed English songs combined with a Vocabulary self-collection (VSS) technique in the treatment to improve students' vocabulary acquisition. The mean pre-test score for 39 students in the eighth grade at an Islamic junior high school was 48,71, and the mean post-test score was 80, 89. The mean results of the pre-test and post-test demonstrated a significant improvement in students' vocabulary mastery. The t-test's p-value (sig-2-tailed) was 0.00, which is less than 0.05. This outcome indicated that Ho was refused but Ha was authorized. It was able to prove that gaining vocabulary in the eighth grade of an Islamic junior high school utilizing an English song and VSS had a positive impact on students' vocabulary mastery. The main teaching implication of this study is that when an English song is combined with specific teaching and learning objectives and supported by learning assessment through VSS, it might assist students in learning English vocabulary effectively.